2014
DOI: 10.1136/bcr-2013-203307
|View full text |Cite
|
Sign up to set email alerts
|

A case of unilateral phthiriasis palpebrarum infestation involving the left eye

Abstract: Phthiriasis palpebrarum is a rare cause of eyelid infestation. We report a case of unilateral phthiriasis palpebrarum. A 28-year-old man presented with moderate itching associated with lacrimation and irritation in the left eye. The initial evaluation of the patient revealed multiple white dots on the left upper eyelashes. Slit-lamp examination revealed multiple nits attached to the base and shaft of the cilia. There was no hyperaemia or discharge present in the conjunctiva and the cornea was clear and shiny. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Phthiriasis palpebrarum is a rare cause of blepharitis due to louse phthirus pubis. 3 It belongs to order Anouplura, family Pthiridae and genus Phthirus. 4 It's body is squat with three pairs of legs, with the second and third pairs carrying heavy pincer like claw.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phthiriasis palpebrarum is a rare cause of blepharitis due to louse phthirus pubis. 3 It belongs to order Anouplura, family Pthiridae and genus Phthirus. 4 It's body is squat with three pairs of legs, with the second and third pairs carrying heavy pincer like claw.…”
Section: Discussionmentioning
confidence: 99%
“…The site of infestation can give a clue to the mode of transmission. 3 It probably reaches the eye by transmission from the pubic area through hands. It is transmitted also via sexual contact or via clothing and towels.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the mechanical removal of the eggs is still a treatment option (13). It has been reported in literature that moxifloxacin and mechanical cleaning are practiced and are effective (14). It has also been reported that only 4% of pilocarpine hydrochloride is effective without mechanical removal (8).…”
Section: Discussionmentioning
confidence: 99%
“…Pthiriasis of the eyelashes usually occurs in both eyelids, although cases with involvement of 1 eye have been reported (5). The eyebrows are rarely involved.…”
Section: Diagnosis: Pthiriasis Of the Eyelashesmentioning
confidence: 99%